Cardiovascular Outcomes in Sleep-Disordered Breathing: Are We Under-estimating? - Yasir, Muhammad; Pervaiz, Amina; Sankari, Abdulghani (Frontiers in Neurology, 2022)
Obstructive sleep apnea is a growing health concern, affecting nearly one billion people worldwide; increasingly recognized as an independent cardiovascular risk factor associated with incident obesity, insulin resistance, hypertension, arrhythmias, stroke, coronary artery disease, and heart failure. The prevalence of obstructive sleep apnea could be underestimated in the previous studies, leading to only modest predictions of cardiovascular outcomes. Using more physiologic data will increase sensitivity for the diagnosis of obstructive sleep apnea. Individuals at high risk of obstructive sleep apnea should be identified so that treatment efforts can be focused on them. This review will assess the evidence for the relationship between obstructive sleep apnea and cardiovascular consequences in the past, present, and future. We will also explore the role of adding physiological data obtained from sleep studies and its ability to enhance the cardiovascular outcome's predictability. Finally, we will discuss future directions and gaps that need further research.